Análisis de los nuevos escenarios universitarios : reflexión previa a los procesos de cambio - Carme Armengol; Diego Castro (Universidad de La Rioja, 2013)
The present paper aims to show a new light on issues that, from our point of view, affect the university while, at the same time, makes us perceive changes as a necessary mechanism of evolution. Three different aspects are discussed: From a contextual point of view we analyse issues external to the University (modern student profiles, knowledge acquired through new Information Technology and new Communication Technology, and a wider understanding of Universities from a more European point of view). The Institution from an organizational point of view, as the Universities have to evolve with the new times. And finally, how academic staff at Universities confronts an always growing number of challenges.